2010
DOI: 10.1016/j.ijpara.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Low infectivity of Plasmodium falciparum gametocytes to Anopheles gambiae following treatment with sulfadoxine–pyrimethamine in Mali

Abstract: Sulfadoxine–pyrimethamine (SP) treatment increases the rate of gametocyte carriage and selects SP resistance-conferring mutations in Plasmodium falciparum dihydrofolate reductase (DHFR) and dihydropteroate synthase (DHPS), raising concerns of increased malaria transmission and spread of drug resistance. In a setting in Mali where SP was highly efficacious, we measured the prevalence of DHFR and DHPS mutations in P. falciparum infections with microscopy-detected gametocytes following SP treatment, and used dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 56 publications
3
38
0
2
Order By: Relevance
“…Second, the QMF assay could be used for gametocyte viability assessments by conducting exflagellation assays after fractionation (45). This would enable a better assessment of the effect of antimalarial drugs on the ability of circulating gametocytes to infect mosquitoes, as it is currently not clear whether all gametocytes in the peripheral blood are viable after treatment (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the QMF assay could be used for gametocyte viability assessments by conducting exflagellation assays after fractionation (45). This would enable a better assessment of the effect of antimalarial drugs on the ability of circulating gametocytes to infect mosquitoes, as it is currently not clear whether all gametocytes in the peripheral blood are viable after treatment (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…As their half-lives are relatively short, this greater potency arises largely from their ability to destroy a wider range of early-stage gametocytes, presumably at their sequestration sites (4,8). However, the exact effect of antimalarial drugs on the viability of more mature P. falciparum gametocytes that continue to circulate after treatment is unclear (9,10).…”
mentioning
confidence: 99%
“…The increase in gametocytemia after treatment is a likely result of the efflux of sequestered gametocytes rather than de novo gametocytogenesis (77). An efflux of not fully mature gametocytes may explain the finding of relatively low infectivity of gametocytes 1 week after SP treatment, despite high densities (30,466), although this could also be related to sporontocidal effects of persisting drug concentrations (229). In general, gametocytemia after treatment is a composite of (i) the ongoing production of gametocytes after initiation of treatment, possibly enhanced by drug-induced stress by slow-acting antimalarials; (ii) the release of sequestrated gametocytes; (iii) the activity of drugs against immature gametocytes, preventing their release into the circulation; and (iv) the activity of drugs against mature gametocytes, clearing the circulating gametocyte population.…”
Section: Effects Of Drugs On Gametocytemiamentioning
confidence: 99%
“…6). Similarly, mutations in the dhfr and dhps genes, encoding SP resistance, were related to increased gametocyte carriage following (30,275,288) or even prior to (288) treatment and to a longer duration of gametocyte carriage than that for wild-type parasites (25). A study by Méndez and colleagues showed that malaria transmission was enhanced 10-fold for parasites with low levels of resistance compared to fully sensitive parasites, despite high SP cure rates in Colombia (274).…”
Section: Gametocytes As An Early Marker For Spread Of Drug Resistancementioning
confidence: 99%
“…Other important risk factors for gametocyte carriage include anaemia [22], durations of the infections, recrudescent infections [23], fever [24], mixed infections [23,25] and drug treatment [26,27]. …”
Section: Introductionmentioning
confidence: 99%